2013
DOI: 10.1074/jbc.m112.407296
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Stress Regulates Rat Mandibular Cartilage Thinning under Compressive Mechanical Stress

Abstract: Background: The molecular mechanisms of mechanical stress-induced cartilage thinning remain largely unknown. Results: Endoplasmic reticulum stress (ERS) was activated in chondrocytes during mechanical stress loading. ERS inhibition suppressed the apoptosis and restored the proliferation and cartilage thinning. Conclusion: ERS regulates mechanical stress-induced cartilage thinning. Significance: Our data demonstrate a novel pathological role for ERS and provide new insight into the treatment of temporomandibula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 34 publications
2
67
0
Order By: Relevance
“…Osteoarthritis (OA) is a prevalent disorder characterized by accelerated chondrocyte terminal differentiation and extracellular matrix degradation in the cartilage of movable joints . OA is often caused by acute and chronic traumatic joint injuries .…”
Section: Introductionmentioning
confidence: 99%
“…Osteoarthritis (OA) is a prevalent disorder characterized by accelerated chondrocyte terminal differentiation and extracellular matrix degradation in the cartilage of movable joints . OA is often caused by acute and chronic traumatic joint injuries .…”
Section: Introductionmentioning
confidence: 99%
“…It may also interact with other steroid receptors or thyroid receptors in a similar way 36. Furthermore, Calr was shown to be involved in cartilage thinning of mandibular cartilage in a rat model that studied the effects of compressive mechanical loading 37. In our forced running experiment, we see a similar induction of Calr expression upon stress, but not in the Dio2 knockout mice, possibly giving the knockout mouse an advantage against the formation of OA-like degradation or cartilage thinning.…”
Section: Discussionmentioning
confidence: 68%
“…Furthermore, our present study showed the effect of BIO was more significantly on the late loading stage (7 d). Our previous studies demonstrated that under compressive mechanical force stimulation, cartilage thinning was mostly mediated by apoptosis in the early stage at 4 d, and the inhibtion of apoptosis can partly rescue the cartilage thinning. However, the proliferation inhibition occurred more apparently in the late stage at 7 d. Therefore, it can be explained why the BIO treatment was more apparent in the late stage.…”
Section: Discussionmentioning
confidence: 97%
“…Each group was randomly divided into four subgroups with 12 animals in each subgroup, namely control (Con: Only injected with vehicle, that is, phosphate buffered saline, in one side of condyle), GSK3β inhibitor BIO alone (rats from Con subgroup injected with BIO in the opposite side of vehicle injection), Force (F: loaded with compressive mechanical force and injected with vehicle in one side of condyle), Force plus BIO (F + BIO: rats from F subgroup injected with BIO in the opposite side of vehicle injection). All of the rats in the F and F + BIO subgroup were loaded with compressive mechanical forces onto their TMJ as being previously described . In brief, the lower incisors of the rats were coated with the resin so that the two hooks made of 0.025‐inch stainless steel wire could not fall off.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation